2020
DOI: 10.1038/s41467-020-16386-3
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease associated mutation E46K of α-synuclein triggers the formation of a distinct fibril structure

Abstract: Amyloid aggregation of α-synuclein (α-syn) is closely associated with Parkinson's disease (PD) and other synucleinopathies. Several single amino-acid mutations (e.g. E46K) of α-syn have been identified causative to the early onset of familial PD. Here, we report the cryo-EM structure of an α-syn fibril formed by N-terminally acetylated E46K mutant α-syn (Ac-E46K). The fibril structure represents a distinct fold of α-syn, which demonstrates that the E46K mutation breaks the electrostatic interactions in the wil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 56 publications
2
95
0
Order By: Relevance
“…The N-terminal interaction hotspot on the monomer contains several lysine residues, which may be attracted to the highly negatively charged Cterminus of the oligomer. Conversely, αS amyloid fibrils possess both exposed disordered N-and C-termini flanking a rigid Greek-key fibril core, as observed in structural models determined by solid-state NMR and cryo-electron microscopy (18)(19)(20)(21)(22). In this way, αS fibrils also have a "fuzzy-coat" made of disordered C-termini (~residues 97-140) in addition to a "fuzzy-coat" made of disordered N-termini (~residues 1-36), providing the potential for αS monomers to interact with either the N-or C-termini of the fibrils (Figure 7).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The N-terminal interaction hotspot on the monomer contains several lysine residues, which may be attracted to the highly negatively charged Cterminus of the oligomer. Conversely, αS amyloid fibrils possess both exposed disordered N-and C-termini flanking a rigid Greek-key fibril core, as observed in structural models determined by solid-state NMR and cryo-electron microscopy (18)(19)(20)(21)(22). In this way, αS fibrils also have a "fuzzy-coat" made of disordered C-termini (~residues 97-140) in addition to a "fuzzy-coat" made of disordered N-termini (~residues 1-36), providing the potential for αS monomers to interact with either the N-or C-termini of the fibrils (Figure 7).…”
Section: Discussionmentioning
confidence: 95%
“…Under the conditions used here, near neutral pH and higher ionic strength, elongation is the predominant mechanism over surface-mediated secondary nucleation (54). The ability to template on the fibril is dependent on an accessible structured core (55), the core dynamics (21,56), and the orientation of the monomer-fibril interaction. Previous work from our group has shown that increased dynamics in the core reduces the seeding capacity of αS fibrils (56), and that N-N, rather than N-C, monomer interactions promote fibril formation (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Primary sequence of the wild-type α-Syn fibril core (aa 37-99). Charged residues are shown in colored bold letters and those interacting in the structures of acetylated wild-type (PDB 6A6B; [120]) and E46K (PDB 6L4S; [121]) α-Syn fibrils are connected by black and red solid lines, respectively. Intermolecular interactions are marked by transverse parallel lines.…”
Section: Relevance Of Electrostatic Charges On Fibrillationmentioning
confidence: 99%
“…Indeed, with respect to the wild type, the E46K variant reshapes the above-mentioned electrostatic network, and forms a smaller fibril core (residues 45-99) and a distinct fold. This is of utmost relevance with regard to the pathogenic mechanism, as E46K fibrils are less resistant to proteases and mechanical stress and, therefore, more prone to propagation [121].…”
Section: Relevance Of Electrostatic Charges On Fibrillationmentioning
confidence: 99%